Pengaruh dukungan sosial terhadap pertumbuhan pasca trauma pada korban difabel akibat bencana gempa - Harsono, Yudi Tri; Nurmalitasari, Femmi; Retnowati, Sofia (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
The earthquake occurring in Yogyakarta in 2006 left long term consequences, especially to those who experienced disability as a result of the disaster. Post traumatic growth is an individual’s positive interpretation of negative experiences or feelings as result of his struggles in overcoming life challenges. This research aims to explore the role of social support in post traumatic growth on diffable survivors of Yogyakarta earthquake. The subjects were survivors of Yogyakarta earthquake in 2006 (N = 51) who suffered upper and lower limbs disability in arms, feet, and spinal cord. Data were collected using Post Traumatic Growth Scale and Sosial Support Scale. The multiple regression analysis suggested that social support significantly contributed to posttraumatic growth among survivors with disabilities of the Yogyakarta earthquake.